The chessmen - May, Peter, 1951- (May, Peter, 1951- Lewis trilogy, 2015)
Ex-Detective Inspector Fin McLeod discovers a light aircraft at the bottom of a spontaneously drained loch while investigating illegal activity on the estate of a poacher and former childhood friend.